Change in Hematologic Indices over Time in Pediatric Inflammatory Bowel Disease Treated with Azathioprine - Soman, Sherman (Springer International Publishing, 2012)
Azathioprine leads to changes in mean corpuscular volume (MCV) and white blood cell (WBC) indices reflecting efficacy or toxicity. Understanding the interactions between bone marrow stem cells and azathioprine could highlight abnormal response patterns as forerunners for hematologic malignancies. This study gives a statistical description of factors influencing the relationship between MCV and WBC in children with inflammatory bowel disease treated with azathioprine. We found that leukopenia preceded macrocytosis. Macrocytosis is therefore not a good predictor of leukopenia. Further studies will be necessary to determine the subgroup of patients at increased risk of malignancies based on bone marrow response.